Management of health information of nepalese labour migrants - Rajendra Karkee; Minani Gurung; Lisasha Poudel; Chiranjivi Baral; Pratik Adhikary; Radheshyam Krishna KC; Sundip Gurung; Vasil Gajdadziev; Patrick Duigan; Montira Inkochasan; Kolitha Prabhash Wickramage; Ganesh Gurung (BMC, 2023)
Abstract Introduction The monitoring and improvement of the health of labour migrants (LMs) require sufficient health data to be recorded and managed. In this context, this study was conducted to explore the management of health information of Nepalese labour migrants (NLMs). Methods This is an explorative qualitative study. Stakeholders involved directly or indirectly in maintaining the health profile of NLMs were first mapped, physically visited, and any documents or information were collected. Then, sixteen key informant interviews were conducted among these stakeholders related to labour migrants' health information management and challenges. A checklist extracted information from the interviews, and a thematic analysis was carried out to summarize the challenges. Results Government agencies, non-governmental organizations, and government approved private medical centers are involved in generating and maintaining the health data of NLMs. The Foreign Employment Board (FEB) records deaths and disabilities of NLMs while at work abroad and these health records are also maintained in an online portal called Foreign Employment Information Management System (FEIMS) under the Department of Foreign Employment (DoFE). Health assessment of NLMs is a mandatory procedure before departure, which is done through the government-approved pre-departure private medical assessment centers. The health records from these assessment centers are first recorded in paper-based form and then entered into an online electronic form to be stored by the DoFE. The filled-up paper forms are sent to District Health Offices, which further report the data to the Department of Health Services (DoHS), Ministry of Health and Population (MoHP) and associated governmental infectious diseases centers. However, there is no formal health assessment of NLMs upon arrival to Nepal. Key informants raised various issues and concerns in maintaining health records of NLMs, which were grouped into three themes: lack of interest to develop a unified online system; need of competent human resources and equipment; and developing a set of health indicators for migrant health assessment. Conclusion The FEB and government-approved private assessment centers are the main stakeholders in keeping the health records of outgoing NLMs. The current migrant health record keeping procedure in Nepal is fragmented. The national Health Information Management Systems does not effectively capture and categorize the health record of NLMs. There is a need to effectively link national health information system with premigration health assessment centers; and potentially develop a migrant health information management system by systematically keeping health records electronically with relevant health indicators on departing and arriving NLMs.